Development of Case Method and Team Based Project Based Textbooks to Improve Students' Science Process Skills in Plant Morphology Courses - Suriani, Cicik (Universitas Negeri Medan, 2024)
Textbooks are books that teachers and students use in learning activities.Textbooks contain learning materials and instructional learning activities that are in accordance with the learning plan that has been prepared by the teacher. Textbooks based on Case method and team-based projects can direct students to carry out several science process skills that are integrated into the learning activities contained in the textbook.This study aims to determine the role of Plant Morphology textbooks based on case methods and teambased projects in improving the science process skills of Biology students. This type of research is descriptive quantitative. This Plant Morphology textbook was developed using the ADDIE development model with stages of analysis, design, development, implementation and evaluation and has been tested for its feasibility. The subject of this study is a plant morphology textbook based on case methods and teambased projects used in learning plant morphology courses. The object of the study is the science process skills of Biology students at the State University of Medan which include ability interpret, predict, analyze data, group, design, conclude and communicate. The results of the study showed that the average value of the ability to interpret 79.4 (high), predict 78.4 (high), analyze data 79.6 (high), group 78.9 (good), design 80 (good), conclude 86 (very good), communicate 86.5 (very good). The number of students who have science process skills with a good category is 90.9% and those who have a less good category are 9.1%.